Satellite-Based Monitoring of Atmospheric Greenhouse Gases: A Real-Time Observation - Garba, Auwal; Zakari, Zakari Aminu; Abdulkadir, Adamu; Bah, Kinga Muhammad; Yusuf, Anas; Yamta, Yainiya (Darul Yasin Al Sys, 2025)
To enhance our understanding of the sources and sinks of greenhouse gases (GHGs), particularly carbon dioxide and methane, it is vital to monitor their atmospheric concentrations in near real time and at high spatial resolution. This study proposes a novel approach involving a constellation of miniature satellites equipped with compact spectrometers possessing nanometer-scale spectral resolution. Climate change, one of the most pressing global challenges, exerts profound impacts across environmental, social, and economic domains. Effective monitoring and assessment are therefore essential to inform policy decisions and mitigate its consequences. Remote sensing technology has emerged as an indispensable tool in climate change research, offering the ability to observe, evaluate, and predict environmental changes on a global scale. By utilizing satellite imagery, aerial surveys, and other sensing methods, scientists and policymakers can collect robust datasets, monitor long-term climate trends, and make evidence-based decisions. The integration of miniaturized satellite spectrometers represents a significant advancement in the effort to improve the timeliness and accuracy of GHG monitoring.